Resin composition for thin-walled flame-retardant molded products and thin-walled flame-retardant molded products
A polyarylene sulfide resin with functional groups and surface-treated inorganic fillers addresses flame retardancy and strength issues, providing a resin composition with improved thin-wall flame retardancy and mechanical strength for electronic and electrical components.
Patent Information
- Application Number
- JP2020212323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-22
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Polyarylene sulfide resins with small particle fillers exhibit low viscosity and flame retardancy issues during combustion, leading to drips and reduced flame retardancy, while existing methods focus on strength enhancement without addressing flame retardancy.
A polyarylene sulfide resin with functional groups like hydroxy, amino, or carboxy groups at its terminals, combined with a surface-treated inorganic filler using organic silane, titanate, or epoxy compounds, to create a resin composition with enhanced flame retardancy and strength.
The composition achieves excellent thin-wall flame retardancy while maintaining mechanical strength, suitable for applications in electrical and electronic components.
Smart Images

Figure 0007619798000001 
Figure 0007619798000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for thin-walled flame-retardant molded articles, which comprises a polyarylene sulfide resin and a surface-treated inorganic filler, and which has excellent flame retardancy while maintaining excellent strength, and to a thin-walled flame-retardant molded article obtained from the resin composition. [Background technology]
[0002] Polyarylene sulfide resin is an engineering plastic that is excellent in chemical resistance, heat resistance, mechanical properties, etc. For this reason, polyarylene sulfide resin is widely used as a metal substitute material in applications such as electrical and electronics, vehicle-related, aircraft, and housing facilities, taking advantage of its excellent properties. In particular, materials to which small particle size fillers are added to polyarylene sulfide resins have high fluidity and strength, so their use in thin-walled and small molded products is being considered. However, polyarylene sulfide resins to which small particle size fillers are added have low viscosity, and often cause dripping during combustion tests, which reduces flame retardancy. As a method for improving the strength of polyarylene sulfide resins, a method of functionalizing the ends of polyarylene sulfide to improve adhesion with fillers is known, as disclosed in Patent Document 1, but no description is made regarding flame retardancy. In addition, Patent Document 2 discloses that strength can be improved by performing surface treatment on inorganic fillers, but no description is made at all regarding functionalization of polyarylene sulfide, and no description is made regarding flame retardancy. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-89925 A [Patent Document 2] WO2019 / 009234 publication Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a resin composition which has excellent flame retardancy when used in a thin wall while maintaining excellent strength. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have discovered that a resin composition comprising a polyarylene sulfide resin having at least one functional group selected from the group consisting of a hydroxy group, an amino group, and a carboxy group at its terminal, and an inorganic filler that has been surface-treated with at least one surface treatment agent selected from the group consisting of an organic silane compound, an organic titanate compound, and an epoxy compound, is a resin composition that exhibits excellent flame retardancy in a thin wall while maintaining excellent strength, and have arrived at the present invention.
[0006] Specifically, the above-mentioned object is achieved by a resin composition for thin-walled flame-retardant molded products, which contains 100 parts by weight of a polyarylene sulfide resin (A component) consisting of (A-1) 10 to 100% by weight of a polyarylene sulfide resin (A-1 component) having at least one functional group selected from the group consisting of a hydroxy group, an amino group, and a carboxy group at its terminal, and (A-2) 0 to 90% by weight of a polyarylene sulfide resin (A-2 component) not containing the above-mentioned functional group at its terminal, and 5 to 90 parts by weight of (B) an inorganic filler (B component) that has been surface-treated with at least one surface treatment agent selected from the group consisting of an organic silane compound, an organic titanate compound, and an epoxy compound.
[0007] The present invention will be described in detail below.
[0008] (Component A: polyarylene sulfide resin) The polyarylene sulfide resin used as component A in the present invention is a polyarylene sulfide resin (component A-2) consisting of 10 to 100% by weight of a polyarylene sulfide resin (component A-1) having at least one functional group selected from the group consisting of a hydroxy group, an amino group, and a carboxy group at its terminal, and 0 to 90% by weight of a polyarylene sulfide resin not having the above functional group at its terminal.
[0009] These polyarylene sulfide resins may include those composed of, as their constituent units, for example, p-phenylene sulfide units, m-phenylene sulfide units, o-phenylene sulfide units, phenylene sulfone units, phenylene sulfide ketone units, phenylene sulfide ether units, diphenylene sulfide units, phenylene sulfide units containing a substituent, and phenylene sulfide units containing a branched structure. Among these, those containing 70 mol % or more, particularly 90 mol % or more of p-phenylene sulfide units are preferred, and poly(p-phenylene sulfide) is more preferred.
[0010] The method for producing the polyarylene sulfide resin is not particularly limited, and the resin is polymerized by a known method. For example, the methods described in U.S. Patent Nos. 4,746,758 and 4,786,713, JP-A-2013-522385, JP-A-2012-233210, and JP-A-5167276 are included. These methods involve directly heating a diiodoaryl compound and solid sulfur without a polar solvent to polymerize them.
[0011] The method includes an iodization step and a polymerization step. In the iodization step, an aryl compound is reacted with iodine to obtain a diiodoaryl compound. In the subsequent polymerization step, the diiodoaryl compound is polymerized with solid sulfur using a polymerization terminator to produce a polyarylene sulfide resin. Iodine is generated in gas form in this step, which is recovered and reused in the iodization step. Iodine is essentially a catalyst.
[0012] A representative example of solid sulfur used in the above-mentioned preparation method is cyclooctasulfur (S8) in which eight atoms are bonded at room temperature. However, the sulfur compound used in the polymerization reaction is not limited, and any form that is solid or liquid at room temperature can be used.
[0013] Representative diiodoaryl compounds used in the above-mentioned production method include at least one selected from the group consisting of diiodobenzene, diiodonaphthalene, diiodobiphenyl, diiodobisphenol, and diiodobenzophenone. Also, derivatives of iodoaryl compounds to which an alkyl group or a sulfone group is bonded, or to which oxygen or nitrogen is introduced, are used. Iodoaryl compounds are classified into different isomers depending on the bonding position of the iodine atom, and preferred examples of these isomers are compounds in which iodine is symmetrically located at both ends of the molecule of the aryl compound, such as p-diiodobenzene, 2,6-diiodonaphthalene, and p,p'-diiodobiphenyl. The content of the iodoaryl compound is preferably 500 to 10,000 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.
[0014] Representative examples of polymerization terminators used in the above-mentioned production method include monoiodoaryl compounds, benzothiazoles, benzothiazolesulfenamides, thiurams, dithiocarbamates, aromatic sulfide compounds, etc. Preferred examples of monoiodoaryl compounds include at least one selected from the group consisting of iodobiphenyl, iodophenol, iodoaniline, and iodobenzophenone. Benzothiazoles Among them, preferred examples include at least one selected from the group consisting of 2-mercaptobenzothiazole and 2,2'-dithiobisbenzothiazole. Preferred examples of benzothiazole sulfenamides include at least one selected from the group consisting of N-cyclohexylbenzothiazole 2-sulfenamide, N,N-dicyclohexyl-2-benzothiazole sulfenamide, 2-morpholinothiobenzothiazole, benzothiazole sulfenamide, dibenzothiazole disulfide, and N-dicyclohexylbenzothiazole 2-sulfenamide. Preferred examples of thiurams include at least one selected from the group consisting of tetramethylthiuram monosulfide and tetramethylthiuram disulfide. Preferred examples of dithiocarbamates include at least one selected from the group consisting of zinc dimethyldithiocarbamate and zinc diethyldithiocarbamate. A preferred example of the aromatic sulfide compound is at least one selected from the group consisting of diphenyl sulfide, diphenyl disulfide, diphenyl ether, biphenyl, and benzophenone.
[0015] Here, the arylene group can be a p-phenylene group, an m-phenylene group, an o-phenylene group, a substituted phenylene group, etc. Specifically, the substituted phenylene group is a phenylene group optionally substituted with one or more of F, Cl, Br, C1-C3 alkyl, trifluoromethyl, C1-C3 alkoxy, trifluoromethoxy, trifluoromethylthio, dimethylamino, cyano, (C1-C3 alkyl)SO2-, (C1-C3 alkyl)NHSO2-, (C1-C3 alkyl)2NSO2-, and NH2SO2-.
[0016] When producing component A-1, it is necessary that at least one functional group selected from the group consisting of a hydroxy group, an amino group, and a carboxy group is substituted on the conjugated aromatic ring skeleton in the polymerization terminator. The hydroxy group, the carboxy group, and the amino group each have a peak at 3200 to 3600 cm in the FT-IR spectrum. -1, 1600~1800cm -1 , 3300~3500cm -1 The content of the polymerization terminator is preferably 1 to 30 parts by weight based on 100 parts by weight of the solid sulfur.
[0017] The method of introducing the reactive functional group into the polyarylene sulfide resin is not particularly limited, and the resin is polymerized by a known method, but a method of using a polymerization terminator having at least one functional group selected from the group consisting of one or more hydroxyl groups, amino groups, and carboxyl groups on a conjugated aromatic ring skeleton can be mentioned.The conjugated aromatic ring skeleton used in the polymerization terminator can be, for example, diphenyl disulfide, monoiodobenzene, thiophenol, 2,2'-dibenzothiazolyl disulfide, 2-mercaptobenzothiazole, N-cyclohexyl-2-benzothiazolyl sulfenamide, 2-(morpholinothio)benzothiazole, N,N'-dicyclohexyl-1,3-benzothiazole-2-sulfenamide, etc.
[0018] As an example, a suitable polymerization method for producing a polyarylene sulfide resin having a terminal group structure of a carboxy group includes a step of polymerizing a diiodo aromatic compound and a reactant containing elemental sulfur, and adding a compound having a carboxy group while proceeding with the polymerization reaction step to substitute a functional group in the terminal group of the polyarylene sulfide main chain.
[0019] In the above-mentioned production method, a polymerization catalyst may be used, and a representative example of the polymerization catalyst is a nitrobenzene-based catalyst. A preferred example of the nitrobenzene-based catalyst is at least one selected from the group consisting of 1,3-diiodo-4-nitrobenzene, 1-iodo-4-nitrobenzene, 2,6-diiodo-4-nitrophenol, iodonitrobenzene, and 2,6-diiodo-4-nitroamine. The content of the polymerization catalyst is preferably 0.01 to 20 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.
[0020] A typical example of the reaction conditions of the production method is to proceed for 1 to 30 hours while increasing the temperature and decreasing the pressure from the initial reaction conditions of 180 to 250°C and 50 to 450 Torr (6.7 to 60 kPa) to the final reaction conditions of 270 to 350°C and 0.001 to 20 Torr (0.00013 to 2.7 kPa). The preferred initial reaction conditions are a temperature of 180°C or higher and a pressure of 450 Torr (60 kPa) or lower, taking into account the reaction rate, and the preferred final reaction conditions are a temperature of 350°C or lower and a pressure of 20 Torr (2.7 kPa) or lower, taking into account the thermal decomposition of the polymer. However, the polymerization reaction conditions are not particularly limited since they depend on the structural design and production rate of the reactor and are known to those skilled in the art. The reaction conditions can be appropriately set by those skilled in the art, taking into account the process conditions.
[0021] By using this polymerization method, it is possible to obtain a polyphenylene sulfide resin having excellent cost performance without the need to substantially reduce the chlorine content and the sodium content.
[0022] The polyphenylene sulfide resin of the present invention may also contain polyphenylene sulfide resins obtained by other polymerization methods.
[0023] The content of A-1 component in component A is 10 to 100% by weight, preferably 30 to 80% by weight, and more preferably 40 to 70% by weight, based on 100% by weight of component A. If the content is less than 10% by weight, the compatibility between the filler and the resin is insufficient, resulting in poor strength and thin-wall flame retardancy.
[0024] The weight average molecular weight of component A is preferably 65,000 to 80,000, more preferably 67,000 to 78,000, and even more preferably 69,000 to 76,000. The weight average molecular weight was measured by high-temperature GPC.
[0025] (Component B: Surface-treated inorganic filler) The inorganic filler used as component B in the present invention must be surface-treated with at least one surface treatment agent selected from the group consisting of organic silane compounds, organic titanate compounds, and epoxy compounds. If the filler is not surface-treated with one of these surface treatment agents, the strength and thin-wall flame retardancy will be inferior.
[0026] Examples of inorganic fillers that can be used in the present invention include potassium titanate, silicon carbide, calcium silicate, wollastonite, talc, mica, attapulgite, ferrite, calcium silicate, calcium carbonate, magnesium carbonate, glass beads, zeolite, milled fiber, calcium sulfate, and the like.
[0027] The content of component B is 5 to 90 parts by weight, preferably 15 to 75 parts by weight, and more preferably 25 to 65 parts by weight, relative to 100 parts by weight of component A. If the content is less than 5 parts by weight, strength and flame retardancy are poor, and if it exceeds 90 parts by weight, strand collection by extrusion kneading is not possible.
[0028] The resin composition of the present invention may contain other thermoplastic resins within the range that does not impair the effects of the present invention. Examples of other thermoplastic resins include general-purpose plastics such as polyethylene resins, polypropylene resins, and polyalkyl methacrylate resins, engineering plastics such as polyphenylene ether resins, polyacetal resins, aromatic polyester resins, liquid crystal polyester resins, polyamide resins, cyclic polyolefin resins, and polyarylate resins (amorphous polyarylate, liquid crystal polyarylate), and so-called super engineering plastics such as polyether ether ketone, polyetherimide, polysulfone, and polyether sulfone.
[0029] The resin composition of the present invention may contain, within the scope of the effect of the present invention, antioxidants and heat resistance stabilizers (hindered phenols, hydroquinones, phosphites, and their substituted derivatives, etc.), weather resistance agents (resorcinols, salicylates, benzotriazoles, benzophenones, hindered amines, etc.), release agents and lubricants (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, various bisamides, bisureas, polyethylene wax, etc.), pigments (cadmium sulfide, phthalocyanine, carbon black, etc.), dyes (nigrosine, etc.), crystal nucleating agents (talc, silica, kaolin, clay, etc.), plasticizers (p-octyl ether, ethyl ether, butyl ... and the like), antistatic agents (alkyl sulfate-type anionic antistatic agents, quaternary ammonium salt-type cationic antistatic agents, nonionic antistatic agents such as polyoxyethylene sorbitan monostearate, betaine-type amphoteric antistatic agents, etc.), flame retardants (red phosphorus, phosphate esters, melamine cyanurate, hydroxides such as magnesium hydroxide and aluminum hydroxide, ammonium polyphosphate, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, brominated epoxy resin, or combinations of these brominated flame retardants with antimony trioxide, etc.) and other polymers can be added.
[0030] (Production of resin composition) The resin composition of the present invention can be produced by mixing the above-mentioned components simultaneously or in any order using a mixer such as a tumbler, a V-type blender, a Nauter mixer, a Banbury mixer, a kneading roll, an extruder, etc. Melt kneading using a twin-screw extruder is preferred, and if necessary, it is preferred to feed any component into the other melt-mixed components from a second feed port using a side feeder or the like.
[0031] The resin extruded as described above is directly cut and pelletized, or strands are formed and then the strands are cut by a pelletizer and pelletized. When it is necessary to reduce the influence of external dust during pelletization, it is preferable to purify the atmosphere around the extruder. The shape of the obtained pellets may be a general shape such as a cylinder, a prism, or a sphere, but is more preferably a cylinder. The diameter of such a cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and even more preferably 2 to 3.5 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and even more preferably 2.5 to 4 mm.
[0032] (About molded products) Molded articles made of the resin composition of the present invention can be obtained by molding the pellets produced as described above. Preferably, they are obtained by injection molding or extrusion molding. Injection molding includes not only ordinary molding methods, but also injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including a method of injecting a supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, multi-color molding, sandwich molding, and ultra-high speed injection molding. Molding can be performed using either a cold runner method or a hot runner method. In addition, extrusion molding can produce various extrusion molded products, sheets, films, and the like. Sheets and films can also be molded using an inflation method, a calendar method, a casting method, and the like. Furthermore, it is possible to mold the resin composition of the present invention into a heat-shrinkable tube by applying a specific stretching operation. It is also possible to mold the resin composition of the present invention into a molded article by rotational molding, blow molding, and the like. Effect of the Invention
[0033] The resin composition of the present invention is a thin-walled resin composition having excellent flame retardancy while maintaining excellent strength, and is therefore useful for applications such as electric and electronic parts and vehicle parts, and the industrial effects thereof are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] The present inventors currently consider the best embodiment of the present invention to be one that embodies the preferred ranges of the above-mentioned requirements, and representative examples thereof are described in the following examples, although the present invention is not limited to these embodiments. EXAMPLES
[0035] [Evaluation of resin composition] (1) Tensile breaking strength The measurement was performed in accordance with ISO527 (measurement condition: 23°C). The test pieces were molded in the following manner. The larger this value, the better the mechanical strength of the resin composition. (2) Flexural strength The measurement was performed in accordance with ISO178 (measurement condition: 23°C). The test pieces were molded in the following manner. The larger this value, the better the mechanical strength of the resin composition. (3) Flame retardancy (0.25 mm) Measurements were performed in accordance with the UL94, V flammability test. The test pieces were molded using the following method. The evaluation method was in accordance with the UL94, V flammability test.
[0036] [Examples 1 to 13, Comparative Examples 1 to 8] A polyarylene sulfide resin and an inorganic filler were melt-kneaded using a vented twin-screw extruder in the respective compounding amounts shown in Tables 1 and 2 to obtain pellets. The vented twin-screw extruder used was TEX30α-38 (fully meshing, co-rotating) manufactured by Japan Steel Works, Ltd. The extrusion conditions were a discharge rate of 20 kg / h, a screw rotation speed of 200 rpm, a vacuum degree of the vent of 3 kPa, and the extrusion temperature was 320 °C from the first feed port to the die part. The inorganic filler was supplied from the second feed port using the side feeder of the extruder, and the polyarylene sulfide resin was supplied to the extruder from the first feed port. Here, the first feed port refers to the feed port farthest from the die, and the second feed port refers to the feed port located between the die and the first feed port of the extruder. The obtained pellets were dried in a hot air circulation dryer at 130 °C for 6 hours, and then test pieces for evaluating the tensile fracture strength test and the flexural strength test were molded at a cylinder temperature of 320 °C and a mold temperature of 140 °C using an injection molding machine (EC160NII-4Y manufactured by Toshiba Machine Co., Ltd.). In addition, for the test piece for evaluating the flame retardancy, the pellets obtained by the above melt-kneading were dried in a hot air circulation dryer at 130 °C for 6 hours, and then a film was formed at a cylinder temperature of 320 °C using a sheet film forming machine (SMZ-40 mm extruder manufactured by Technovel Corporation), and a test piece with a thickness of 0.25 mm was prepared.
[0037] Each component with the symbol notation in Tables 1 and 2 is as follows. <Component A> A-1-1: A polyphenylene sulfide resin having a carboxy group at the terminal obtained by the following production method [Production Method 1] Into a 5 L reactor equipped with a thermocouple capable of measuring the internal temperature of the reactor, a vacuum line for nitrogen filling and vacuum application, a reactant containing 5130 g of p-diiodobenzene (p-DIB), 450 g of sulfur, and 4 g of 1,3-diiodo-4-nitrobenzene as a reaction initiator was heated to 180 °C to be completely melted and mixed, and then starting from the initial reaction conditions of 220 °C and 350 Torr, the polymerization reaction was allowed to proceed while gradually increasing the temperature and decreasing the pressure until the final reaction temperature was 300 °C and the pressure was 1 Torr or less. When the polymerization reaction had proceeded 80% ( The progress of the polymerization reaction was determined by measuring the relative ratio of the current viscosity to the target viscosity [(current viscosity / target viscosity)×100(%)]. The current viscosity was measured by taking a sample during polymerization and using a viscometer. ), 25 g of 2,2'-dithiobisbenzothiazole was added as a polymerization inhibitor, and the reaction was allowed to proceed for 1 hour. Next, when the polymerization reaction proceeded to 90%, 51 g of 4-iodobenzoic acid was added, and the reaction was allowed to proceed for 10 minutes under a nitrogen atmosphere, and then the vacuum was gradually increased to 0.5 Torr or less, and the reaction was allowed to proceed for 1 hour, and then the reaction was terminated, and a polyarylene sulfide resin having a carboxy group at the main chain end was synthesized. The resin after the reaction was completed was produced in the form of pellets using a small strand cutter. The polyarylene sulfide resin was analyzed by FT-IR, and the peak intensity was about 1600 to 1800 cm on the spectrum. -1 The presence of a carboxyl group peak was confirmed in the FT-IR spectrum at about 1400 to 1600 cm -1 When the height intensity of the ring stretch peak that appears at about 1600 to 1800 cm is taken as 100%, -1 The relative height intensity of the peak was about 3.4%, and the weight average molecular weight was 71,000.
[0038] A-1-2: Polyphenylene sulfide resin having amino groups at the terminals, obtained by the following manufacturing method: [Manufacturing method 2] In a 5L reactor equipped with a thermocouple capable of measuring the internal temperature of the reactor, and a vacuum line capable of filling with nitrogen and applying a vacuum, reactants including 5130 g of paradiiodobenzene (p-DIB), 450 g of sulfur, and 4 g of 1,3-diiodo-4-nitrobenzenemercaptobenzothiazole as a reaction initiator were heated to 180°C to completely melt and mix, and then polymerization reaction was carried out while gradually increasing the temperature and decreasing the pressure from initial reaction conditions of 220°C and 350 Torr to a final reaction temperature of 300°C and a pressure of 1 Torr or less. When the polymerization reaction had progressed to 80% (the degree of progress of the polymerization reaction was determined by measuring the relative ratio of the current viscosity to the target viscosity [(current viscosity / target viscosity) x 100 (%)]. The current viscosity was measured by taking a sample during polymerization and using a viscometer), 25 g of 2,2'-dithiobisbenzothiazole was added as a polymerization terminator, and the reaction was carried out for 1 hour. Next, when the polymerization reaction had progressed to 90%, 51 g of 4-iodoaniline was added, and the reaction was allowed to proceed for 10 minutes under a nitrogen atmosphere, and then the reaction was gradually reduced to 0.5 Torr or less and allowed to proceed for 1 hour. The reaction was then terminated, and a polyarylene sulfide resin having an amino group at the end of the main chain was synthesized. The resin in which the reaction was completed was produced in the form of pellets using a small strand cutter. The polyarylene sulfide resin was analyzed by FT-IR, and found to have a peak at about 3300 to 3500 cm in the spectrum. -1 The presence of an amino group peak at about 1400 to 1600 cm was confirmed in the FT-IR spectrum. -1 When the height intensity of the ring stretch peak that appears at about 3300 to 3500 cm is taken as 100%, -1 The relative height intensity of the peak was about 1.4%, and the weight average molecular weight was 70,000.
[0039] A-1-3: Polyphenylene sulfide resin having a hydroxyl group at the end, obtained by the following manufacturing method: [Manufacturing method 3] In a 5L reactor equipped with a thermocouple capable of measuring the internal temperature of the reactor, and a vacuum line capable of filling with nitrogen and applying a vacuum, reactants including 5130 g of paradiiodobenzene (p-DIB), 450 g of sulfur, and 4 g of 1,3-diiodo-4-nitrobenzenemercaptobenzothiazole as a reaction initiator were heated to 180°C to completely melt and mix, and then polymerization reaction was carried out while gradually increasing the temperature and decreasing the pressure from initial reaction conditions of 220°C and 350 Torr to a final reaction temperature of 300°C and a pressure of 1 Torr or less. When the polymerization reaction had progressed to 80% (the degree of progress of the polymerization reaction was determined by measuring the relative ratio of the current viscosity to the target viscosity [(current viscosity / target viscosity) x 100 (%)]. The current viscosity was measured by taking a sample during polymerization and using a viscometer), 25 g of 2,2'-dithiobisbenzothiazole was added as a polymerization terminator, and the reaction was carried out for 1 hour. Next, when the polymerization reaction had progressed to 90%, 51 g of 4-iodophenol was added and the reaction was allowed to proceed for 10 minutes under a nitrogen atmosphere, and then the reaction was gradually reduced to 0.5 Torr or less and allowed to proceed for 1 hour. The reaction was then terminated to synthesize a polyarylene sulfide resin having a hydroxyl group at the end of the main chain. The resin in which the reaction was completed was produced in the form of pellets using a small strand cutter. The polyarylene sulfide resin was analyzed by FT-IR and showed a peak at about 3200 to 3600 cm in the spectrum. -1 The presence of a hydroxyl group peak was confirmed in the FT-IR spectrum. -1 When the ring stretch peak height intensity that appears at about 3200 to 3600 cm is taken as 100%, -1 The relative height intensity of the peak was about 1.4%, and the weight average molecular weight was 71,400.
[0040] A-1-4: Polyphenylene sulfide resin having a carboxyl group at the end, obtained by the following manufacturing method: [Manufacturing method 4] Polymerization was carried out in the same manner as in Production Method 1 except that the amount of the polymerization terminator was 25 g, and a polyarylene sulfide resin having a carboxy group at the main chain terminal was synthesized. The polyarylene sulfide resin was analyzed by FT-IR, and the presence of a peak of the carboxy group at about 1600 to 1800 cm -1 was confirmed on the spectrum. Also, on the FT-IR spectrum, when the height intensity of the Ring stretch peak appearing at about 1400 to 1600 cm -1 was taken as 100%, the relative height intensity of the peak at about 1600 to 1800 cm -1 was about 3.3%. The weight average molecular weight was 60,000.
[0041] A-2-1: A polyphenylene sulfide resin having a phenyl group at the terminal obtained by the following production method [Production Method 5] Into a 5 L reactor equipped with a thermocouple capable of measuring the internal temperature of the reactor and a vacuum line capable of nitrogen filling and applying vacuum, 5130 g of para-diiodobenzene (p-DIB), 450 g of sulfur, and a reactant containing 4 g of 1,3-diiodo-4-nitrobenzene mercaptobenzothiazole as a reaction initiator were heated to 180° C. to be completely melted and mixed, and then starting from the initial reaction conditions of 220° C. and 350 Torr, the polymerization reaction was allowed to proceed while gradually increasing the temperature and decreasing the pressure step by step until the final reaction temperature was 300° C. and the pressure was 1 Torr or less. When the polymerization reaction had proceeded 80% (the progress of the polymerization reaction was determined by measuring the relative ratio of the current viscosity to the target viscosity [(current viscosity / target viscosity)×100(%)]. The current viscosity was measured with a viscometer by sampling a sample during the polymerization progress.), 60 g of 2,2'-dithiobisbenzothiazole was added as a polymerization terminator, and after allowing the reaction to proceed for 10 minutes under a nitrogen atmosphere, the vacuum was gradually increased to 0.5 Torr or less, and after reaching the target viscosity, the reaction was terminated to synthesize a polyarylene sulfide resin having a phenyl group at the main chain terminal. The resin after the reaction was produced in pellet form using a small strand cutter machine. The weight average molecular weight was 72,000.
[0042] <Component B> B-1: SH-1250S (Kinseimatec Co., Ltd., Wollastonite, particle size: 9.5 μm, aminosilane coupling surface treatment) B-2: TISMO D102 (Otsuka Chemical Co., Ltd., potassium titanate whisker, particle size: 0.3-0.6 μm, epoxy-based coupling surface treatment) B-3: SE-TA-13 (Talc, manufactured by Miyoshi Kasei Co., Ltd., particle size: 5 μm, aminosilane coupling surface treatment)
[0043] B-4: Calcium carbonate surface-treated with an organic titanate coupling agent obtained by the following method: [Manufacturing method] Calcium carbonate powder (KSS-1000, manufactured by Calfine Co., Ltd.) having an average primary particle size of 2.1 μm was placed in a stirring mixer, and 2 parts by weight of tetraisopropyl titanate (Orgatix TA-1, manufactured by Matsumoto Fine Chemical Co., Ltd.) was added per 100 parts by weight of calcium carbonate. The mixture was stirred and mixed at 60° C. for 15 minutes to obtain calcium carbonate surface-treated with an organic titanate coupling agent.
[0044] B-5: Mica surface-treated with an aminosilane coupling agent obtained by the following method [Manufacturing method] Mica powder (A-11, manufactured by Matsuo Sangyo Co., Ltd.) having an average primary particle size of 3.0 μm was placed in a stirring mixer, and 3.0 parts by weight of 3-aminopropyltrimethoxysilane (KBM-903, manufactured by Shin-Etsu Chemical Co., Ltd.) was added per 100 parts by weight of mica. The mixture was stirred and mixed at 60°C for 15 minutes to obtain mica surface-treated with an aminosilane coupling agent.
[0045] B-6: Kaolin surface-treated with an epoxy compound obtained by the following method [Manufacturing method] Kaolin powder (A-11, manufactured by Tomoe Engineering Co., Ltd.) having an average primary particle size of 5.0 μm was placed in a stirring mixer, and 2.0 parts by weight of 3-glycidoxypropylmethyldimethoxysilane (KBM-402, manufactured by Shin-Etsu Chemical Co., Ltd.) was added per 100 parts by weight of kaolin, followed by stirring and mixing at 60°C for 15 minutes to obtain kaolin surface-treated with an epoxy compound. b-7: NAI-Talc JA-13R (Talc, particle size 5μ, amino acid surface treatment, manufactured by Miyoshi Chemical Industries, Ltd.) b-8: SH-1250 (Kinseimatec Co., Ltd., Wollastonite, particle size: 9.5 μm) b-9: BITREX (JEF Mineral Co., Ltd., potassium titanate, particle size: 0.3-0.6 μm) b-10: KHP-25 (Talc, manufactured by Hayashi Kasei Co., Ltd., particle size: 4.75 μm)
[0046] [Table 1]
[0047] [Table 2]
Claims
1. The resin composition for thin-walled flame-retardant molded products contains, per 100 parts by weight of a polyarylene sulfide resin (A component) consisting of (A-1) 10 to 100% by weight of a polyarylene sulfide resin (A-1 component) having at least one functional group at its terminal selected from the group consisting of hydroxyl groups, amino groups, and carboxyl groups, and (A-2) 0 to 90% by weight of a polyarylene sulfide resin (A-2 component) not containing said functional group at its terminal, and (B) 5 to 90 parts by weight of at least one inorganic filler selected from the group consisting of wollastonite, potassium titanate whiskers, and calcium carbonate (B component) which has been surface-treated with at least one surface treatment agent selected from the group consisting of organic silane compounds, organic titanate compounds, and epoxy compounds.
2. 2. The resin composition for thin-walled flame-retardant molded products according to claim 1, wherein the weight average molecular weight of component A is 65,000 to 80,000.
3. 3. A thin-walled flame-retardant molded article obtained from the resin composition according to claim 1 or 2, which has a flame retardancy rank of V-0 at a thickness of 0.25 mm in a UL94 flame retardancy test.
Citation Information
Patent Citations
Thermoplastic resin composition for surface mounting part
JP1995102173A
Resin composition
JP2007023078A
Resin composition
JP2017125140A
Polyarylene sulfide resin composition, and article made thereof
JP2019031589A
Polyarylene sulfide resin composition
JP2019089925A